2014
DOI: 10.1111/disa.12113
|View full text |Cite
|
Sign up to set email alerts
|

Post‐tsunami relocation of fisher settlements in South Asia: evidence from the Coromandel Coast, India

Abstract: The tsunami that struck the coasts of India on 26 December 2004 resulted in the large-scale destruction of fisher habitations. The post-tsunami rehabilitation effort in Tamil Nadu was directed towards relocating fisher settlements in the interior. This paper discusses the outcomes of a study on the social effects of relocation in a sample of nine communities along the Coromandel Coast. It concludes that, although the participation of fishing communities in house design and in allocation procedures has been lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…However, planning without appropriate participation can lead to measures that fail to support recovery [80,81] or have unintended negative consequences on development [79,82,83]. After reviewing post-disaster reconstruction processes in ten countries, Schilderman and Lyons [84] concluded that, while top-down, donor-driven recovery processes resulted in technically safer housing, the process failed to support overall resilience.…”
Section: Participationmentioning
confidence: 99%
“…However, planning without appropriate participation can lead to measures that fail to support recovery [80,81] or have unintended negative consequences on development [79,82,83]. After reviewing post-disaster reconstruction processes in ten countries, Schilderman and Lyons [84] concluded that, while top-down, donor-driven recovery processes resulted in technically safer housing, the process failed to support overall resilience.…”
Section: Participationmentioning
confidence: 99%
“…The relevance of the outside world for fisher affairs manifested itself most clearly in the post-tsunami period, when relief and rehabilitation were important concerns. It was then that ur panchayats realized the relevance of having representatives capable of negotiating with outside agencies, and replaced older, illiterate leaders with younger men who had been to school and knew how to speak with officials (Gomathy 2006;Bavinck et al 2015).…”
Section: Promoting Wellbeing Through Interventions With Governmentmentioning
confidence: 99%
“…4 The villages that were substantially rebuilt in the post-tsunami era have, however, undergone an important change with government insisting that individual titles be provided to houses (see Bavinck et al 2015). 5 Factionalism is not a permanent condition but a setback that can affect any ur panchayat in the course of time.…”
Section: Endnotesmentioning
confidence: 99%
“…The literature reviewed (Ahmed & McEvoy, 2014;Athukorala & Resosudarmo, 2005;Bavinck et al, 2014;Chacko, Kulkarni, & Eldho, 2012;Chandra, 2003;Cronin & Guthrie, 2011; * In the case studies, not much distinction is made between climate related impacts versus disaster risk. Extreme events all seem to come under the purview of 'disasters' and attribution to climate change is limited.…”
Section: Appendix 7 : Literature Review On Disaster and Climate-impacmentioning
confidence: 99%
“…The selected articles (Ahmed & McEvoy, 2014;Barenstein & Iyengar, 2010;Bavinck et al, 2014;Chacko et al, 2012;Chandra, 2003;Cronin & Guthrie, 2011;Duyne Barenstein & Amaratunga, 2015;Ghani, 2001;Gopalakrishnan & Kuberan, 2005;S. Gupta et al, 2003;Iqbal, 2010;Joerin et al, 2012;Kayastha & Yadava, 1985;Shaw & Ahmed, 2010;van Eerd, 2008) emphasize the design aspects and problems during the implementation of the resettlement plan.…”
Section: Appendix 7 : Literature Review On Disaster and Climate-impacmentioning
confidence: 99%